(untitled) (International Journal of Physiotherapy, 2023)
Background: Self-reported measures represent patients’ perspectives toward their disease, but their performance levels may vary. Performance-based measures mimic the patient’s functional activity movement, which helps evaluate specific task components, including how the therapist approached the task. Both measures report the patient’s functional level from the patient’s or therapist’s perspective. The study was done to determine the correlation between self-reported and performance-based measures outcomes in non-traumatic stiff shoulder pathologies. Method: Self-reported outcome measure scores were recorded using the Shoulder Pain And Disability Index (SPADI), Disabilities of Arm, Shoulder, and Hand (DASH), and Patient Specific Functional Scale (PSFS). Performance-based measures scores of the shoulder were given using function-related tests of the shoulder: 1) Hand to the neck, 2) Hand to scapula 3) Hand to the opposite scapula. Result: Inferential statistics were done using the Pearson correlation test, and the significance level was set at p<0.05. Pearson correlation test showed: 1) Weak statistically significant correlation between SPADI versus function-related test 1(r= 0.32), DASH versus Function-related test 1(r= 0.31), and function-related test 2(r= 0.31) and PSFS versus function-related test 1(r= 0.36). 2) Other correlations were Very Weak and non-significant. Conclusion: As the correlation between all three self-reported measures and each of the three function-related tests has become weak, there is a need to include both self-reported and performance-based measures in assessing patients with non-traumatic stiff shoulder pathologies.